Produção acadêmica do curso de licenciatura em matemática da uft/araguaína: - SILVA, Edson Caitano da (Universidade Federal do Tocantins, 2023)
This study aims to present a study on the Course Completion Work (TCC) defended in the scope of the degree course in Mathematics of the Federal University of Tocantins (UFT), Campus of Araguaína whose themes address the trends in Mathematics Education and training Of teachers. To analyze the productions made in the period of 2005 - 2014. For this we create categories of analysis, from which we get to discuss and present the results. Subsequently, we analyze these categories in the light of some theorists, such as: D'Ambrósio (1997); Hairstyle (2004); Bicudo (1992), who directed our results. We intend with this study not only to present a picture of the academic production of the course, but also to contribute with the future researches of the graduates of this one of the degree course of the UFT. Our qualitative research, of the documentary type.